THE BRYOPHYTA CHECK-LIST FOR B6 SQUARE OF TURKEY - Keçeli, Tamer; Ursavaş, Serhat; Abay, Gökhan (Bartın Üniversitesi, 2011)
This study includes the current list based on researchs done up to now for B6 grid square mosses (Musci), liverworts (Hepaticae) and hornworts (Anthocerotae) according to Henderson (1961)'s Turkey grid system. 326 taxa belonging to 39 families and 120 genera are determined from B6 grid square mosses. The richest moss families according to their genera number are given respectively: Pottiaceae (27), Brachytheciaceae (16), Amblystegiaceae (9), Ditrichaceae (7) and Hypnaceae (5), the richest families according to their taxa number are; Pottiaceae (84), Brachytheciaceae (46), Orthotrichaceae (22), Grimmiaceae (21), Bryaceae (18), Amblystegiaceae (13) and Fissidentaceae (12). In genera category the richest ones according to their taxa variety are Orthotrichum (19), Bryum (18), Grimmia (14), Tortula (14), Fissidens (12), Syntrichia (11) and Didymodon (10). From B6 grid square, 67 taxa belonging to 27 families and 33 genera for Hepaticae and 3 taxa belonging to 1 family and 3 genera for Anthocerotae are determined. In this square, from Hepaticae and Anthocerotae the richest families according to their genera number are respectively; Aytoniaceae (3), Lophoziaceae (3) and Anthocerotaceae (3), the richest genera according to their taxa number are Riccia (10), Porella (5) and Cephaloziella (4).

Bu çalışma, Henderson (1961)'ın Türkiye kareleme sistemine göre B6 karesi içerisinde şimdiye kadar yapılmış olan karayosunu (=Musci), ciğerotları (=Hepaticae) ve boynuzsu ciğerotları (=Anthocerotae) araştırmalarına dayanan güncel bir listeyi içermektedir. B6 karesinden karayosunları için 39 familya ve 120 cinse ait 326 takson tespit edilmiştir. Bu kare içerisinde, içerdiği cins sayısı bakımından en zengin karayosunu familyaları sırasıyla; Pottiaceae (27), Brachytheciaceae (16), Amblystegiaceae (9), Ditrichaceae (7) ve Hypnaceae (5); içerdiği takson sayısı açısından en zengin familyalar ise; Pottiaceae (84), Brachytheciaceae (46), Orthotrichaceae (22), Grimmiaceae (21), Bryaceae (18), Amblystegiaceae (13) ve Fissidentaceae (12) dir. Cins kategorisinde ise takson çeşitliliği açısından en zengin olanlar; Orthotrichum (19), Bryum (18), Grimmia (14), Tortula (14), Fissidens (12), Syntrichia (11) ve Didymodon (10)'dur. B6 karesinden, Hepaticae sınıfı için 27 familya ve 33 cinse ait 67 takson ve Anthocerotaceae sınıfı için ise 1 familya ve 3 cinse ait 3 takson tespit edilmiştir. Bu kare içerisinde, Hepaticae ve Anthocerotae sınıfından içerdiği cins sayısı bakımından en zengin familyalar sırasıyla, Aytoniaceae (3), Lophoziaceae (3) ve Anthocerotaceae (3); takson sayısı bakımından en zengin cinsler ise, Riccia (10), Porella (5) ve Cephaloziella (4)' dır.
TÜRKİYE'NİN B6 KARESİNİN BRYOPHYTA KONTROL LİSTESİ